The impact of macro and micro shocks on the productivity improvements of the main public airports in Thailand - Benjaparn, Nattawat; Rungsuriyawiboon, Supawat (Thammasat Review of Economic and Social Policy, 2021)
This paper studies the productivity measurement of the 6 main public airports in Thailand since Suvarnabhumi Airport (BKK) opened in 2007 to the year before the COVID-19 pandemic happened. This paper also discusses the effect of both the macro and micro shocks such as the global financial crisis between 2008 to 2009 and the big flooding in 2011 on the productivity growths of the airports. This paper is the first study that employs the Malmquist Total Factor Productivity Index (MPI) model to measure the productivity growths of Thailand’s airports. The finding reveals that both shocks declined the performances of the airports. Within the study period, the airports promote productivity growth by emphasizing the adoption of new technologies than the operation of workers. The average productivity growth of the airports was 4.5 percent a year in this period implying that there existed productivity progress in this industry prior to the COVID-19 outbreak.